Impactos da pluviosidade para a colonização micorrízica em diferentes ambientes do semiárido - Gomes, Kaio Henrique Pinheiro (2020)
Among the ecological relationships we find in nature, positive mutualistic interactions stand out, such as mycorrhizal associations, a very common relationship in nature that is established between fungi and plant roots. In places where abiotic conditions are adverse, plant species that make such an association tend to stand out in relation to the others due to the greater ease of collection of limiting resources. Considering the stress gradient hypothesis, positive interactions are expected to increase as the environment becomes more stressful, but it is not yet known exactly how mutualistic interactions, such as mycorrhizae, respond to this stress. From this, we tested the hypothesis of whether mycorrhizal associations become more common in more stressful environments, such as drier environments. In this work, we seek to understand how mycorrhizal associations vary in locations with different abiotic severities and how much this association is necessary for vegetation to survive in these environments. For this, we collected the fine roots of the most representative woody species from three locations with different rainfall and aridity rates in the Brazilian semiarid region to make a comparative analysis of the mycorrhizal colonization rate in these environments. The results obtained showed that the driest and most arid environment is the one with the greatest mycorrhizal colonization among the three. The other two sites had a higher rate of facultative mycorrhizal colonization, which also justifies a lower rate of colonization in these environments, however, other factors may also interfere in this rate. Therefore, we can see that rainfall can be an important factor for the variation of mycorrhizal colonization